Volume 1: Offshore Technology; Ocean Space Utilization 2003
DOI: 10.1115/omae2003-37170
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Mega-Float Equipped With Novel Wave Energy Absorber

Abstract: The hydroelastic response is significant from the viewpoint of the structural design of a Mega-Float. Equipping a Mega-Float with some additional structures, such as vertical plates, is one of the ways to reduce the hydroelastic response easily. However, in general, wave drift force acting on the Mega-Float may be increased, when the Mega-Float is equipped with the additional structures to reduce the response. In the present study, we developed a novel additional structure that was effective in the reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…By means of the theoretical solutions and experimental tests, Ohta et al [12] investigated the performance of a submerged vertical plate attached to the fore-end of a VLFS. Masanobu et al [13] further developed the vertical anti-motion plate with slits and the inverted-L type anti-motion plate and concluded that the inverted-L type anti-motion plate can achieve more desirable efficiency in reducing the hydroelastic responses of the VLFS. Takagi et al [14] proposed another anti-motion device with a simple submerged vertical box attached at the fore-end of the VLFS, in which small-scale experiments were conducted and the results correlated well with the analytical solutions.…”
Section: Introductionmentioning
confidence: 97%
“…By means of the theoretical solutions and experimental tests, Ohta et al [12] investigated the performance of a submerged vertical plate attached to the fore-end of a VLFS. Masanobu et al [13] further developed the vertical anti-motion plate with slits and the inverted-L type anti-motion plate and concluded that the inverted-L type anti-motion plate can achieve more desirable efficiency in reducing the hydroelastic responses of the VLFS. Takagi et al [14] proposed another anti-motion device with a simple submerged vertical box attached at the fore-end of the VLFS, in which small-scale experiments were conducted and the results correlated well with the analytical solutions.…”
Section: Introductionmentioning
confidence: 97%
“…Takagi et al [6] concluded that, when a box-shaped body is attached to an edge of a VLFS, it reduces not only the deformation but also the shearing force and the moment of the platform, also attaining a good anti-motion performance. Masanobu et al [7] proposed the additional wall with slits and the inverted-L type structures to mitigate the hydroelastic response of the VLFSs. They found that the drift force and the vertical displacement can be suppressed by providing slits for the anti-motion device.…”
Section: Introductionmentioning
confidence: 99%
“…These horizontal plates help in generating reverse flow at the aft-end of the plate that counteract with the incident wave. Curtain wall with slits (Masanobu et al 2003) attached to the fore-end of VLFS have also been proposed to mitigate the hydroelastic response through eddies generated by the slits. Pinkster (1997) also borrowed the air-cushion technology used in hovercrafts and surface effect ships (SES) to reduce the hydroelastic response of VLFS.…”
Section: Introductionmentioning
confidence: 99%